RNA-binding protein HuR inhibition induces multiple programmed cell death in breast and prostate cancer - Lanjing Wei; Sung Hae Kim; Ahlam M. Armaly; Jeffrey Aubé; Liang Xu; Xiaoqing Wu (Cell Communication and Signaling)
Abstract The RNA-binding protein Hu antigen R (HuR) plays a pivotal role in cancer progression, and previous studies have demonstrated its involvement in suppressing cell death in cancer. However, the precise mechanisms underlying HuR inhibition-induced cell death remain elusive. Here, we investigated the impacts of HuR functional inhibition via the small molecule inhibitor KH-3 on cell proliferation, colony formation, and cell death across multiple cancer cell lines, with an emphasis on breast and prostate cancers. KH-3 treatment induced apoptotic cell death of various cancer cell lines, as well as autophagy-associated cell death and ferroptosis. Remarkably, KH-3-induced cell death was partially rescued by an autophagy inhibitor and a ferroptosis inhibitor. The anti-tumor effects of KH-3 were further validated in two mouse xenograft models of human prostate cancer. Mechanistically, KH-3 reduced the expression of HuR targets involved in apoptosis and ferroptosis suppression, including cFLIP and SLC7A11, respectively. Moreover, cFLIP silencing enhanced Caspase-8 activation as well as PARP cleavage in both breast cancer and prostate cancer cells. Both KH-3-induced pharmacological HuR inhibition and RNA interference-mediated HuR knockdown reduced the expression of SLC7A11. Additionally, KH-3 also reduced XIAP and Survivin, enhancing the activation of multiple caspases and leading to apoptosis. This study highlights the critical roles of HuR in programmed cell death regulation, advocating HuR inhibition as a promising anti-tumor strategy for cell-death-inducing cancer therapy.